Analysis of the school boards served to adolescents of the educational network of the Guaribas Valley (Research, Society and Development, 2018)
The objective of this study was to conduct a quali-quantitative evaluation of the nutritional aspects of the menus offered to adolescents in municipal schools in the Guaribas Valley. This is a descriptive analysis and documentary type carried out in elementary schools, part-time, urban and rural areas of a teaching network, carried out through the rescue and analysis of the menus offered in the period from July 2016 to January of 2017. The menus were examined qualitatively, according to the National Program of School Education. The quantitative analysis was performed according to the Brazilian Food Composition Table. To verify the suitability of the macro and micronutrient nutrients, the age range of 11 to 16 years was chosen. Values lower than those required by law for carbohydrates, lipids, proteins, calcium, vitamin A, fiber, magnesium and zinc were found, whereas vitamin C and iron values were higher than recommended. The meals offered by the schools examined were in disagreement with the current legislation, for macro and micronutrients, their compositions deserve to be re-evaluated.